Detection of alignment changes at the open surface of a confined nematic liquid crystal sensor - McCamley, M; Ravnik, M; Artenstein, A; Opal, S; Zumer, S; Crawford, G (2009)
An open surface optical sensor based on nematic liquid crystal contained in square shaped wells was fabricated. Structures and structural transitions associated with changes in surface anchoring conditions were optically detected using polarizing microscopy. A phenomenological Landau-de Gennes model was applied to model the response of the sensor. Simulated optical micrographs were compared with experiments to understand the nematic profiles and to control and optimize the sensor in a specific regime. Distinct optical patterns were detected when the sensor was exposed to air and to water. A structural transition in the nematic structure was observed, driven by changes in the anchoring strength at the open surface of the sensor. Anchoring strength was varied by adding a homeotropic surfactant (sodium dodecyl sulfate) to strongly planar de-ionized water. The transition can be controlled using sensor parameters such as well depth and aspect ratio. © 2009 American Institute of Physics.